Analisis Yuridis Tingginya Cerai Gugat Istri terhadap Suami pada Masa Pandemi Covid-19 (Studi Penelitian di Mahkamah Syar’iyah Lhoksukon) - Eko Gani PG; Eka Chyntia (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
The number of divorce cases that occurred during the Covid-19 pandemic is a concern. Divorce applications at the Lhoksukon Sharia Court are mostly from ordinary or middle class people who apply for divorce for various reasons. Article 38 Law no. 1 of 1974 regarding